1983
DOI: 10.1038/301511a0
|View full text |Cite
|
Sign up to set email alerts
|

Chemolithoautotrophic metabolism of anaerobic extremely thermophilic archaebacteria

Abstract: Several types of extremely thermophilic archaebacteria have recently been isolated from solfataric water holes, hot springs and hot sea floors. It has been shown that some of them can live using sulphur respiration of reduced carbon substrates as a source of energy, a type of metabolism previously described for the eubacterium Desulfuromonas. We report here that several extremely thermophilic archaebacteria can live with carbon dioxide as their sole carbon source, obtaining energy from the oxidation of hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 193 publications
(96 citation statements)
references
References 10 publications
2
94
0
Order By: Relevance
“…The new isolates, including strain FUT, grew chemolithoautotrophically on hydrogen by reducing molecular sulfur to H,S. Growth depended obligately on the presence of both H, and So, indicating that the organisms were H,-So lithoautotrophs (14). Sulfur could not be replaced by sulfite, tetrathionate, L-( -)-cystine, or sulfate.…”
Section: Resultsmentioning
confidence: 92%
“…The new isolates, including strain FUT, grew chemolithoautotrophically on hydrogen by reducing molecular sulfur to H,S. Growth depended obligately on the presence of both H, and So, indicating that the organisms were H,-So lithoautotrophs (14). Sulfur could not be replaced by sulfite, tetrathionate, L-( -)-cystine, or sulfate.…”
Section: Resultsmentioning
confidence: 92%
“…This organism, an extremely thermophilic anaerobic Archaebacterium [19], grows autotrophically at 85°C at the expense of sulfur reduction to hydrogen sulfide. The operation of the reductive pentose phosphate cycle and of the reductive acetylCoA/carbon monoxide dehydrogenase pathway in C 0 2 fixation has been excluded.…”
Section: )mentioning
confidence: 99%
“…Under anaerobic conditions, this organism grows with elemental sulfur, thiosulfate, glutathione (oxidized form) or L-cystine as terminal electron acceptor (Sako et al, 2001). From the aspect of respiration, the genus Pyrobaculum is uniquely variable among the hyperthermophilic archaea, which may be closest to the common ancestor of all organisms; P. aerophilum is not only a microaerophile but also a nitrate, nitrite, thiosulfate, arsenate and selenite reducer (Völkl et al, 1993;Huber et al, 2000); Pyrobaculum islandicum reduces sulfur and iron(II) compounds (Huber et al, 1987;Kashefi & Lovely, 2000;Vargas et al, 1998); Pyrobaculum organotrophum reduces sulfur compounds (Huber et al, 1987); Thermoproteus neutrophilus, which is classified in the genus Thermoproteus although the phylogenetic analysis of 16S rDNA indicated that it should be reclassified as a Pyrobaculum species (Ito et al, 1998), is a sulfur reducer (Fischer et al, 1983); Pyrobaculum arsenaticum is arsenite reducer . This diversity of respiration in close relatives suggests that this genus may show a good example of the evolution of respiration and also show the nature of adaptation to the aerobic environment.…”
Section: Introductionmentioning
confidence: 99%